The Use of Selenium and Oestrous Synchronisation Protocols to Improve Oestrous Response and Fertility of Merino Ewes. - Hlatshwayo, Sibonelo Mmelokuhle; Muritala, Ismaila; Lehloenya, Khoboso Christina (Jurnal Sain Veteriner, 2025)
Selenium (Se) deficiency is linked to poor reproductive performance in sheep, while indiscriminate use of pharmaceuticals in oestrous synchronisation imposes economic burden on sheep farmers. Optimisation of interventions that could improve reproduction in sheep at minimum cost required investigation. This study evaluated the effect of Se-supplementation and oestrous synchronisation protocols on reproductive performance of Merino ewes and immunity of their lambs. Sixty ewes were randomly grouped in a 2x2 factorial design: Se-supplementation plus equine chorionic gonadotropin (eCG) (n=15), Se-supplementation plus male effect (n=15), non-Se-supplementation plus eCG (n=15) and non-Se-supplementation plus male effect (n=15).  Ewes were hand mated with 8 Merino rams at 48 and 60 hours after CIDR removal. Data on oestrous response, distribution of oestrus, conception and lambing rates were analyzed using Chi-square test, while onset and duration of oestrus, gestation length, glutathione peroxidase, cortisol, oetradiol-17β, progesterone and Immunoglobulin G concentrations were analysed using PROC GLM with SAS®. Se-supplemented ewes had a higher (P<0.05) oestrous response at 36 hours after CIDR removal. Se-supplementation had no effect (P>0.05) on the onset, duration and distribution of oestrus, gestation length conception and lambing rate. Se-supplementation decreased (P<0.05) the cortisol concentration of ewes at CIDR removal and IgG concentration of lambs 12 hours after lambing. The eCG protocol increased (P<0.05) the number of ewes that displayed signs of oestrus at 24, 36 and 48 hours after CIDR removal compared to the male effect. Therefore, Se-supplementation combined with eCG administration improved oestrous response in Merino ewes and is more suitable for fixed-time artificial insemination.